Participação social institucionalizada e a re-produção do espaço urbano da cidade de Várzea Grande – MT - Silva, Rosinaldo Barbosa da (2015)
The production of contemporary urban space carries the contradiction, characteristic of uneven development, where economic walks ahead of the social. This economic determination deepens social inequalities including from the legal framework of urban policy, such as the City Statute, the City Council and Public Hearings - institutionalized participation spaces. For these areas develop the strategies of economic and political groups to maintain their privileges entitling them through laws and institutionalized social participation and, therefore, at the same time, removing / reducing social development possibilities that movements popular fought / fight to get put in the state agenda. We intend, in this way understand the integration strategies of the urban space of the city of Várzea Grande to recent circuit real estate valuation and how this leads to the disintegration of life of residents and urban struggles. Will highlight the tactical alliance between the state and the private that can be perceived within the institutionalized social participation spaces (public hearing / city council), showing how the contradictions of the new legal instruments (the City Statute) has deepened. The issue of popular or contemporary institutionalized participation in the production of urban space we investigated in this study refers to the socio-spatial practices of the inhabitants increasingly devoid of meaning production of human life. This problem is intensified by the transformation of urban space strategy as a meeting place, sociability, social interactions, reproduction of life, manifested by the social use enlarged reproduction of capital space, determining the daily lives of residents mechanically , repeater, split and alienated. The hegemonic force of expanded reproduction of capital produces conflicts, because society is not homogeneous. Conflicts take place in urban areas by playing necessities of life (human achievement) and reproduction of capital (exchange / merchandise). Participation requires the meeting spaces and sociability in urban areas in order to produce a space that matches the needs of society. However, the aggression imposed by the capitalist mode of production transforms the form and content of the production of urban space, producing socio-spatial segregation, separation of social classes, breaking the sociability of meeting the different, directly influencing participation. In addition to reflection on the spaces of social participation institutionalized in the production of urban space also investigate popular participation, emerging from the social movement (becoming) and has the power to produce breaks in the alienated and unequal mode of production of urban space and the question aim to overcome the "representative Democracy". We investigated the relationships in popular residential, where relocate "the poorest among the poor" (Residential Rosewood) and "lower fractions of the middle class" (Condo Ruby and Allotment sun hat), and surrounding residents - which investigated the possibilities of struggles against social inequalities deepen floodplain Grande city, especially in the northern part of the urban area. In this sense, the research aims to analyze the production of a new urban area while producing the deepening socio-spatial segregation in the city of Várzea Grande can produce tensions / demonstrations by the search to the right to the city through social mediation, which seeks to recover the divisions imposed by the existing mode of production.